Proposed P-shaped Microstrip Antenna Array for Wireless Communication Applications - Raad H. Thaher; Noor Baqir Hassan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
In this paper a P-shaped microstrip antenna array is proposed for X-band applications in the frequency range (8.1567-9.3811) GHz .The gain obtained in this frequency range is about 8.305 dBi. The reflection coefficient is less than - 10 dB in the above frequency range. The simulation results were obtained for the optimum parameters using the CST software while the practical test was carried out using Vector Network Analyzer (VNA). The microstrip antenna was manufactured using FR-4 substrate with relative dielectric constant of 4.3 and loss tangent tan⁡〖δ=0.002〗.The simulation and practical results were compared. The size of the antenna array is (33×70×1.6) 〖mm〗^3. This array is suitable for satellite communication, radar application.